Tantangan Anak di Indonesia Dalam Menghadapi Era Global: Kajian Pendidikan Agama Islam - Firman Mansir; Lia Kian; Sofyan Abas; Masyhar Sa’adi (Jayapangus Press, 2022)
This research aims to explain the threats and challenges faced by children in Indonesia. So that readiness and a strong mentality are needed to deal with them, especially in the global era. This study uses a qualitative approach, so that in collecting data through a literature study. Overall, the data are sourced from the literature and some relate to the reality that occurs in the field. The results of this study indicate that the current era of globalization has various kinds of challenges that cannot be avoided. The era of globalization with sophisticated technology poses challenges and threats that continue to grow and a child must be able to face these challenges and threats. For this reason, it is necessary to have direction and guidance that is considered capable of equipping children in the future. It is increasingly difficult to deal with children in the face of sophisticated technology so many cases are found, plus when the Covid-19 pandemic arrives like today, children are increasingly difficult to teach and guide. Thus, the problems faced by many families are children who are difficult to guide and need to be directed by instilling and teaching religious education. So that they can know about life to form an intelligent personality and become thought and pious children.